Penerapan Sistem Informasi Industri di Human Resource Department di PT. XYZ - Edhiargo Toyosito, Rakay; Yazid Bustommy, Abby; Bagus Sumantri, Ida (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2022)
Information systems at this time have made human life easier. Every company, government and educational institution definitely needs an information system because it is very beneficial for many parties. So now many companies are using information systems to support their company's activities. Because the information system itself can make it easier to manage company activities. ". To find out the extent to which the effectiveness and efficiency of the use of "online presence" is necessary, it is necessary to implement an industrial information system. The cost required by HRD to apply for a permit is reduced by Rp. 115,000/year. According to the evaluation of the online presence, the system is very helpful for HRD in storing and processing employee attendance data in the company.